Efficacy, Feasibility, Adherence and Cost Effectiveness of a mHealth Telerehabilitation Program in Low Risk Cardiac Patients: A Study Protocol. - Pastora-Bernal, José Manuel; Hernández-Fernández, Joaquín José; Estebanez Pérez, María José; Molina-Torres, Guadalupe; García López, Francisco José; Martín-Valero, Rocío (MDPI, 2021)
Cardio-telerehabilitation (CTR) programs are a supplement or an alternative to hospital rehabilitation programs providing similar benefits to usual hospital and home care. Despite this statement, implementation in the public and private healthcare environment is still scarce and limited. The main objective of this research was to evaluate the efficacy, feasibility, and adherence of a personalized eight-week mHealth telerehabilitation program in low-risk cardiac patients in the hospital of Melilla (Spain). The secondary aims were to investigate patient satisfaction, identify barriers of implementation and adverse events, and assess cost-effectiveness from a health system perspective. A study protocol for a single center prospective controlled trial was conducted at the Regional Hospital of Melilla (Spain), with a sample size of (n = 30) patients with a diagnosis of low-risk CVD with class I heart failure according to NYHA (New York Heart Association). Outcomes of this study, will add new evidence that could support the use of CTR in cardiac patients clinical guidelines.
Keywords: Sistema cardiovascular - Enfermedades; Rehabilitación - Innovaciones tecnológicas; Medicina - Innovaciones tecnológicas; Análisis coste-beneficio; Fisioterapia; Cardiovascular diseases; Cost-benefit analysis; Physical therapy modalities; Telemedicine; Telerehabilitation